A path in analytical model of school factors and students' achievement in senior secondary school physics in Oyo State (2010)
The study examined school factors (school distance from students' home, class size, government grants, availability of parent teachers association and instructional leadership) as determinants of students' achievement in SS physics in Oyo State, Nigeria. Fifty-four principals and 1,080 students in 54 schools were involved in the survey. Physics Achievement Test and School Questionnaire were used to collect data. The five predictor variables were meaningful and significant to the criterion variable (students' achievement in physics). Instructional leadership contributed the most and class size the least. It is recommended that principals should exert their influence in the schools by making teachers do their work, maintain order and discipline, these are likely to increase students' achievement in physics.